Media Bias and Advertising: Evidence from German Car Magazines - Ralf Dewenter; Ulrich Heimeshoff (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
This paper investigates the existence of a possible media bias by analyzing the impact of automobile manufactures' advertisements on automobile reviews in German car magazines. By accounting for both endogeneity and sample selection we find a positive impact of advertising volumes on test scores. Moreover, also a home bias in terms of higher scores for German cars is observable. We account these results as some evidence for a media bias, induced by the two-sidedness of the markets.
Keywords: L00; L82; C35; 330